Fly fishing in northern New Mexico - Martin, Craig; Ableson, Hugo. (Albuquerque University of New Mexico Press, 2002)
This is a comprehensive guide to over thirty streams and twelve lakes. This revised edition contains new, specialised information on access, equipment, stream characteristics, trout species and size, timing of insect hatches, as well as artificial fly patterns likely to result in success.
Includes bibliographical references.
102582
Keywords: Fly fishing -- New Mexico -- Guidbooks; New Mexico -- Guidebooks